Effect of Enterococcus faecalis Pyelonephritis on the Intracortical Accumulation Kinetics of Gentamicin in Rats - Martial Jullien; Guy Thériault; Michel G Bergeron; Denis Beauchamp (Canadian Journal of Infectious Diseases)
The role of serum levels on the intracortical accumulation kinetics of gentamicin was evaluated in normal and Enterococcus faecalis-infected kidneys using a short term infusion model in conscious rats. Female Sprague-Dawley rats were infused over a period of 6 h with gentamicin achieving individual steady-state serum levels ranging from 0.5 to 20 μg/mL. Pyelonephritis was induced by a direct inoculation of the left kidney with a suspension of E faecalis. This model resulted in severe infection of the left kidney and mild infection of the right kidney. Gentamicin cortical concentrations were analyzed as a function of serum levels by linear regression (least squares regression analysis). Steady-state elevation of serum concentrations of gentamicin was associated with a linear increase of cortical concentrations in normal, and in both left and right infected kidneys. No significant difference in the kinetics of gentamicin uptake was observed between normal and right and left infected kidneys. Therefore, E faecalis pyelonephritis does not modify the intracortical accumulation kinetics of gentamicin.